An Introduction to Architecture and Building Construction: A Starter Module for Freshers of Interior Design - Didem Güneş Yilmaz (International Journal of Architectural Engineering Technology, 2018)
Architecture is an interdisciplinary area itself; a world of design, materials, textures, history, culture, art, technology, construction, visualisation, economics, management and so on. As it consists of many diverse knowledge-areas, the curriculum of architecture is often too loaded with different types of modules. Some modules are delivered only thematically, while some are introductory in order to prepare students to the next core modules. This paper focuses on the content development of the module of Introduction to Architecture and Building Construction, which is delivered to the fresher year of the Department of Interior Architecture and Environmental Design in their spring semestre. The module is required to complete in the four-year curriculum and is formed of two theoretical hours and two practical hours in a week. In accordance with the title as well as the structure of the module, the content was developed in two-folds. The number of the students registered for the module was 24. For the part of Introduction to Architecture, each student was assigned a well-known architect to study, which aimed to make students familiar with the names, their career path, their design approach and building characteristics, the history of movements they followed, their strands in interior design and product design. For the part of Introduction to Building Construction, it was aimed to make the students familiar with the world renowned designs as well as materials and construction technology they used. Using the series of videos explaining the design and construction process of some of the selected buildings in the lectures and the follow-up discussions formed the latter part of the module. Accordingly, the paper explains how the module content was developed, why the rationales were behind and what was aimed to achieve by this kind of structure and content.